2006
DOI: 10.1111/j.1742-4658.2006.05443.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis possesses a functional enzyme for the synthesis of vitamin C, L‐gulono‐1,4‐lactone dehydrogenase

Abstract: Vitamin C (l-ascorbic acid; L-AA) is an important metabolite of plants and animals. It functions as an antioxidant (or pro-oxidant), an enzyme cofactor, an effector of gene expression, and a modulator of reactive oxygen species (ROS)-mediated cell signaling. L-AA is therefore involved in a wide array of crucial physiologic processes, including: biosynthesis of collagen and other hydroxyproline ⁄ hydroxylysine-containing proteins ⁄ peptides; synthesis of secondary metabolites, hormones and cytokines [1] Plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 50 publications
1
50
0
1
Order By: Relevance
“…The characteristic flavin spectrum was absent and the enzyme activity was the same with or without exogenous addition of 100 μM FAD (data not shown). This is similar to the findings with the L-GulL dehydrogenase (GulLDH) enzyme from Mycobacterium tuberculosis [14]. …”
Section: Resultssupporting
confidence: 90%
“…The characteristic flavin spectrum was absent and the enzyme activity was the same with or without exogenous addition of 100 μM FAD (data not shown). This is similar to the findings with the L-GulL dehydrogenase (GulLDH) enzyme from Mycobacterium tuberculosis [14]. …”
Section: Resultssupporting
confidence: 90%
“…The recent discovery of a functional bacterial gene for vitamin C synthesis, the L-gulono-1,4-lactone dehydrogenase of the Mycobacterium tuberculosis pathogen, and the fact that similar proteins are present in many bacterial pathogens and symbionts (Wolucka and Communi, 2006), further support the hypothesis of a eubacterial origin of vitamin C-related genes in the evolution of higher eukaryotes. A common ancestor of green algae and plants had assembled evolutionary novel VTC2 and L-gulono-1,4-lactone dehydrogenase genes, in addition to the more ancient algal GDP-mannose 3 00 ,5 00 -epimerase, thus forming a formidable enzymatic machinery for an extremely efficient production of L-ascorbic acid.…”
Section: Evolution Of Vitamin C Biosynthesis In Plantsmentioning
confidence: 93%
“…This observation provides indirect evidence for the involvement of the putative Lgluono-1,4-lactone dehydrogenases in the de novo synthesis of vitamin C. Clearly, L-galactonolactone dehydrogenase gene was retained and well-conserved in higher plants, but highly mutated or lost in green algae, probably after the acquisition of the L-gluono-1,4-lactone dehydrogenase gene. BLAST searches of eukaryotic and prokaryotic genomes revealed that only few species of bacteria contain a protein similar to the plant L-gulono-1,4-lactone dehydrogenases, and the closest homolog is present in a marine proteobacterium Hahella chejuensis (27% identity) that is closely associated with algal populations, and in some actinobacteria (Wolucka and Communi, 2006). It seems probable, therefore, that an ancient L-gulono-1,4-lactone dehydrogenase gene of a common ancestor of green algae and land plants could be acquired via horizontal gene transfer from an ancient marine eubacterium.…”
Section: Evolution Of Vitamin C Biosynthesis In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ascorbic acid is a well-known antioxidant, and elevated ascorbic acid oxidation to threonic acid, in various other organisms is usually indicative of increased oxidative stress (42). Although an ascorbic acid synthesis pathway has been previously described for M. tuberculosis (43), the oxidative breakdown product of this, threonic acid, most probably induced by elevated hydrogen peroxide, as detected in these isoniazid-resistant strains, has never been described for M. tuberculosis. This may be due to two possible reasons: first, the elevated hydrogen peroxide due to the mutation in katG, and second, the elevated ascorbic acid synthesis by the organism to cope with this, or both.…”
Section: Discussionmentioning
confidence: 98%